2002
DOI: 10.1006/dbio.2002.0678
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the RNA-Binding Protein, hermes, in the Regulation of Heart Development

Abstract: RNA-binding proteins are known to play an important role in a number of aspects of development, although in most cases the precise mechanism of action remains unknown. We have previously described the isolation of an RNA-binding protein, hermes, that is expressed at very high levels in the differentiating myocardium. Here, we report experiments aimed at elucidating the functional role of hermes in development. Utilizing the Xenopus oocyte, we show that hermes is localized primarily to the cytoplasm, can associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 51 publications
6
47
0
Order By: Relevance
“…Importantly, we could rescue these defects by injecting normal versions of the transcripts, at least partially. Previously, we and others have implicated splicing proteins in developmental regulatory events in Xenopus, but it has been difficult to identify the primary targets (Gerber et al 2002;Liu and Harland 2005). Here we used the phenotypes of the affected embryos to identify some misregulated components and extended this using RNA-seq to show that we can analyze missplicing in an unbiased manner.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we could rescue these defects by injecting normal versions of the transcripts, at least partially. Previously, we and others have implicated splicing proteins in developmental regulatory events in Xenopus, but it has been difficult to identify the primary targets (Gerber et al 2002;Liu and Harland 2005). Here we used the phenotypes of the affected embryos to identify some misregulated components and extended this using RNA-seq to show that we can analyze missplicing in an unbiased manner.…”
Section: Discussionmentioning
confidence: 99%
“…RBPMS expression in embryos and adult tissues has been studied by various methodologies in several vertebrate species supporting expression in heart and retinal ganglion cells (Shimamoto et al 1996;Gerber et al 2002;Su et al 2004;Wang et al 2008;Kwong et al 2010;Derrien et al 2012). A survey of a limited set of adult human tissues by poly(A) RNAseq indicated that RBPMS was the most highly expressed in the prostate, followed by colon, adipose tissue, and heart, with RBPMS being higher expressed than RBPMS2 in most tissues (Derrien et al 2012;Supplemental Fig.…”
Section: Rbpms Family Member Expression Patternsmentioning
confidence: 99%
“…Dysregulation of RBPMS family proteins has been reported in cancer (Skawran et al 2008;Miller and Stamatoyannopoulos 2010;Drozdov et al 2012;Hapkova et al 2013; http://www.cbioportal.org/public-portal/) and chronic intestinal pseudo-obstruction (Notarnicola et al 2012). Manipulation of RBPMS levels during embryogenesis suggested functions in X. laevis oocyte maturation (Zearfoss et al 2003), heart and kidney development (Gerber et al 2002), and retinal ganglion cell development (Hornberg et al 2013). In X. laevis RBPMS regulated cleavage of vegetal blastomeres in early embryogenesis (Zearfoss et al 2004) and was suggested to control mRNA processing (Gerber et al 2002;Song et al 2007) and transport of mRNAs along the axon to the axon terminal of retinal ganglion cells (Hornberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nkx2.5 expression is regulated by both XHMGA2 and Smads (Monzen et al, 2008). The RNA-binding protein hermes also regulates Nkx2.5 expression (Gerber et al, 2002). Tbx5, Tbx20, myocardin, and islet1 are transcription factors that interact with Nkx2.5 and GATAs and regulate gene expression in the precardiac region (Stennard et al, 2003, Small et al, 2005, Brade et al, 2007.…”
Section: In Vitro Differentiation Of Pronephros and Molecular Analysimentioning
confidence: 99%